DISSEMINATION OF THE IMPORTANCE OF A MANUAL STORAGE SYSTEM AND PREPARATION FOR THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS AT THE TK. HOSPITAL. III REKSODIWIRYO PADANG - Wahyuni, Annisa (LPPM Univ. Ibn Khaldun Bogor, 2023)
Hospitals have an important role in the basic health needs of society. This of course affects the management and quality of service which can be seen from the medical record administration system, one of which is the aspect of good medical record keeping. This service activity aims to increase the knowledge of officers about the importance of a medical record storage system and preparation for transforming into an Electronic Medical Record System (RME). The service was carried out at the Tk Hospital. III Reksodiwiryo Padang. The activity method begins with the pre and post-tests and then continues with the socialization of the storage system based on Permenkes Number 24 of 2022. The results of the activity obtained an increase in the knowledge of officers about the importance of the medical record storage system with an average score obtained by the participant's pre-test was 49.5, while the average post-test score is 83 with a percentage increase of 66.5%, which means that more than half experience an increase in knowledge. It can be concluded that this activity has a positive impact on the knowledge of the staff at the hospital.